EU Countries Electromobility Ranking Based on Linear Ordering Methods from Economics Perspective - Monika HAMERSKA; Monika ZIOLKO; Patryk STAWIARSKI (Communications of International Proceedings, 2022)
The article concerns the issues of the development of electromobility, which is a significant challenge to the policies of European countries today. The initial part of the analysis is an overview of the current state of knowledge on the level of electromobility in the EU countries and attempts to systematize it in the form of a ranking of countries showing similarities in the studied area. The main part of the study is the created electromobility ranking for EU countries based on selected indicators. The structure and significance of selected electromobility indicators were examined, and then they were visualized how they are shaped in individual countries. The last element of the study is an attempt to classify the study group according to the adopted indicators and similarities between them by the linear ordering method using the Hellwig's development pattern method. The analysis allowed to distinguish 4 clusters characterized by a different level of electromobility development, the most numerous group of which are countries with an average level.
Keywords: electric vehicles; electromobility; ranking; linear ordering method; electromobility level.